Augmenting Blood Profile and Reproduction in Buffaloes of Tribal Areas of Vadodara District (Gujarat) through Appropriate Mineral Mixture Supplementation - Chaudhary, RK; Patel, DC (Indian Journal of Veterinary Sciences and Biotechnology, 2019)
An on-farm trial for 90 days was conducted using 20 anestrus and 20 repeat breeder buffaloes to evaluate the effect of supplementing  appropriate mineral mixtures (AMMs) on their nutrient intake, blood profile, estrus occurrence, and conception. Both anestrus and repeat  breeder buffaloes were randomly allotted to 2 treatments, i.e., T1 (Ionic mineral mixture) and T2 (T1 + 25% extra zinc in the chelate form).  The average intake of DCP, TDN, and copper in anestrus and repeat breeder buffaloes calculated as per information collected from farmers  were almost the same among treatments and as per requirements of animals. The average intake of calcium and phosphorus was higher  by 65% and 45% than the requirements in anestrus and repeat breeder buffaloes. However, Zn intake was lower by about 35% of the  requirement in all treatments. Blood glucose, serum total protein, and serum albumin levels increased marginally on supplementation  of T1 and T2 mineral mixtures for 90 days, particularly in anestrus buffaloes. The serum triglycerides and total cholesterol increased, but  non-significantly (p >0.05), particularly in T1 groups of both anestrus and repeat breeder animals, whereas levels of BUN and creatinine  increased significantly (p
Keywords: Anestrus; Buffalo; Mineral supplementation; Repeat breeder; Return to heat